Comparison of Clinical and Radiographic Outcomes Following Arthroscopic Debridement With Extracellular Matrix Augmentation and Osteochondral Autograft Transplantation for Medium-Size Osteochondral Lesions of the Talus. (June 2021) - Hansen, Oliver B.; Eble, Stephanie K.; Patel, Karan; Cabe, Taylor N.; Sofka, Carolyn; Deland, Jonathan T.; Drakos, Mark C.
Background: Historically, microfracture has been used to treat small talar osteochondral lesions with good results, whereas osteochondral autologous transplantation (OAT) has proven effective for the treatment of larger lesions. It is not clear which method is more effective for medium-sized lesions around the critical size of 150 mm 2, above which microfracture outcomes tend to be poor. The purpose of this study was to determine the potential advantages of OAT augmented with a combination of extracellular matrix and bone marrow aspirate concentrate (ECM-BMAC) compared to debridement with ECM-BMAC (DEB) in the treatment of medium-sized osteochondral lesions of the talus (OLTs). Methods: Clinical and radiographic data were collected retrospectively for patients treated by a single fellowship-trained foot and ankle surgeon. Magnetic resonance images (MRIs) were scored using the Magnetic Resonance Observation of Cartilage Tissue (MOCART) system and were evaluated for the presence of cysts and edema. Fifty-two patients met inclusion criteria, with 25 who received an OAT procedure. Age, body mass index, lesion size, lesion location, and follow-up time were similar between groups. Average MRI follow-up times were 16.7 months for the OAT group and 20.3 months for the DEB group ( P = .38). Results: Patients treated with OAT had significantly higher average total MOCART scores (69 vs 55, P = .04) and significantly lower rates of cyst (14% vs 55%, P < .01), edema (59% vs 90%, P = .04), revision surgery (0% vs 19%, P = .05), and therapeutic injection for pain (4% vs 30%, P = .02) compared to patients treated with DEB. No significant differences were detected in patient-reported outcome scores between groups. Conclusion: The native hyaline cartilage introduced by OAT appears to result in higher-quality repair tissue when compared to DEB, as evidenced by OAT patients' higher MOCART scores and lower rates of cyst and edema. There was no difference in clinical outcome scores, though OAT patients did not require revision surgery or therapeutic injection for pain as frequently as DEB patients. Level of Evidence: Level III, retrospective comparative study.